การศึกษาวิวัฒนาการหุ่นกระบอกไทย : สื่อพื้นบ้านในภูมิภาคตะวันตก : รายงานการวิจัย - ศักดา ปั้นเหน่งเพ็ชร (จุฬาลงกรณ์มหาวิทยาลัย, 1992)
The performing art of puppets as a midium of entertainment has been inherited by the nations which have been developed to a level of culture throughout the world for more than a thousand years. There is evidence that the Thai have enjoyed puppet performances since the Ayudhaya period. At that time the popular performing puppet was called "Hun luang" which means "puppet that belongs to the royal court". It was as popular as other kinds of entertainment in those days : Knon (mask play) and Lakhon (stage play). This type of puppet had developed steadily throughout the Ayudhaya, Thonburi, up to the Rattanakosin period. During the reign of King Chulalongkorn, Rama V of the Chakri dynasty, there was a newkind of puppet, the rod puppet, which was introduced and started to attract the interest of the people. Within a very short period of time, the rod puppet, originating from the northern part of, had become one of the most popular forms of entertainment in Thailand,both inside Bangkok, the capital, and other bigcities. As a result of its popularity, there were quite a number of well known puppet troups. This was the truly golden age of rod puppets. Like other kinds of arts and performing arts in Thailand at that time, rod puppets originated inside a court of royal patronage or a house of high ranking persons in the administration. Then, gradually, they become common property. Perfromances of Thai rod puppets had been given in both royal ceremonies and for folk entertainment for more than half a century.However, when the new kinds of entertainment which were born with modern technology flowed into Thailand from the West at the turn of this century, the popularity of Thai rod puppets both as entertainment and as a folk medium diminished. In consideration of the development of the Tai rod puppet within the Western region of Thailand, there is evident indication that all the rod puppet troups in this area have been inspired and influenced by the attraction of the rod puppet troups form Bangkok during the reign if KingChulalongkorn. SHortly after the first rod puppet troup was created by Khum Tor, a courtier if Prince Damrong, there was proliferation in the number of rod puppet troups in Bangkok, including the very well-known one which belonged to Prince Suthat. At the beginning, Prince Suthat created rod puppets in order to fulfil only his own satisfaction. However, after some time, the fame of the beauty and attractiveness of his puppets spread a far and wide. Eventually, it was organised along professional lines and yield the owner an income. Prince Suthat s rod puppet troup was not known only in Bangkok, but also in other cities, particularly the provinces in the middle region around the capital. At one time, they visited the city of Samusonkhram Province, where the beauty of rod puppets and the skillful performances of puppeteers become a strong inspiration for a young man called Ploy and his wife Sarai to creat their own rod puppet troup. Just by chance, at more or les the same time, they mey Mae Kru Kluab, the famous puppets who taught and translated her shill in rod puppet development in the Western region of Thailand. Sarai and her teacher Kluab had another very able student, called Wong. After some times, he started his rod puppet troup, the Ched Chu Chamnan Silp, which is based in Umpawa, Samutsongkhram. Nowadays, we can no longer have an opportunity to see rod puppets performed by Mea Sarai. In the Western region of Thailand, the only rod puppet troup, which still exists, is the Ched Chu Chamnan Silp of Umpawa, Samutsongkhram, belonging to uncle Wong Ruamsuk. This is the only rod puppet troup of the Western region of Thailand which is still available for publci entertainment and at the same time which makes a great contribution to the preservation of this kind of performing art before it completely vanished.